RISIKO PAJANAN BAHAN PENCEMAR TERHADAP PEKERJA PENGECATAN MOBIL DI PT.STEELINDO MOTOR KOTA PADANG - Erdinur Erdinur; Burhan Muslim; Erick Zicof (Poltekkes Kemenkes Padang, 2021)
Car painting work is one of the jobs that are at great risk of impaired lung function. Paint particles consist of hazardous chemicals such as cadmium, chromium, plumbum, mercury, acrylic resin, isocyanate, and toluene solvents. These materials when proven to enter the respiratory tract can cause lung function disorders. The purpose of this study is to identify hazards, analyze dose-response, analyze exposure and analyze the risk characterization of pollutants. This research is descriptive by analyzing environmental health risks to pollutants around the work environment. The population is all sanding, picking, and painting workers totaling 21 people which become sample. The instruments used in this study were low volume air sampler (LVAS), thermo hygrometers, anemometers, scales, and checklists for observing activity patterns. Data analysis uses stages in environmental risk analysis. Respondents smoke at work as much as 47.6%, and do not use APD 71.4%. Pollutants that exceed the quality standard are dust (0.1538 μg / m3), and Cd (0.0025 μg / m3). RQ value (life time) > 1 for all exposure materials, which means that agent risk is not safe after 30 years of work. Management needs to manage risks such as reducing concentration, exposure time, and frequency of exposure to safe limits by managing risk through a technological approach, socioeconomic approach, and an institutional approach.